Persamaan Gender dalam Al-Qur'an: Tafsir Tematik dan Relevansi Kontemporer - Sapril Sapril; Sakirman Sakirman; Ruslan Ruslan; Moh. Ilyasin; Titi Kadi Ibrahim (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Although gender equality in the Qur’an has been widely discussed in Islamic studies, its meaning is still often reduced to biological sameness or, conversely, used to justify discriminatory social relations. This article aims to analyze the concept of gender equality in the Qur’an through thematic interpretation and explain its relevance to contemporary life. This study used a library research method with a qualitative-descriptive approach. The primary data consisted of Qur’anic verses on the origin of humanity, piety, righteous deeds, moral responsibility, and male-female social relations, while the secondary data consisted of tafsir books, academic books, journal articles, and institutional documents related to gender justice. Data were collected through documentation, selected based on thematic relevance, and analyzed using content analysis through the stages of reduction, classification, interpretation, and conceptual synthesis. The results of the study show that the Qur’an constructs gender equality through five main dimensions, namely ontological equality, spiritual-moral equality, reciprocal social responsibility, substantive justice, and the protection of human dignity. The discussion affirms that biological and social differences cannot be used as a basis for subordination but need to be situated within the framework of maqāṣid al-sharī‘ah, public benefit, and relational ethics. The conclusion of this study affirms that Qur’anic gender equality is relevant to education, family, the public sphere, and modern social governance because it offers a normative foundation for building just, inclusive, and dignified relations. These findings contribute to strengthening the study of thematic interpretation and Islamic gender justice in responding to contemporary social dynamics.